POLITENESS IN OFFICIAL LETTERS - Siti Aisyah; Hardianawati Hardianawati (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
This study aims to explain politeness and describe the potential negative faces in terms of formal invitation letter sentences. This research belongs to the realm of pragmatics and examines data qualitatively. The results of this study indicate that in the invitation letter there is politeness based on Leech's maxims and the potential for negative faces to appear.Keyword: Politeness, face threatening act, official invitation letter